Resilience in LGB Youths: A Systematic Review of Protection Mechanisms - Freitas, Daniela Fonseca; Coimbra, Susana; Fontaine, Anne Marie (Paidéia (Ribeirão Preto), 2017)
Given the mental health disparities among LGB and heterosexual youth, literature has increasingly emphasized the need to identify the mechanisms that promote resilience among sexual minorities. This systematic review sought to answer the question: what are the protection mechanisms against homophobia among LGB youth? Of the 147 references located in the search, 13 studies were analyzed. The identified protection mechanisms were organized by two criteria: specific to sexual orientation or general, and considered to be at the personal, relational and contextual level. Most of the mechanisms revealed to solely promote the positive adjustment in the presence of risk. General protective mechanisms frequently revealed to be more compensatory of the risks than those specific to sexual orientation.